(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The purpose of this paper is to interrogate what makes history a specialised and particular discipline; to ask what does it mean to do history and to know history. I draw on the work of those working within the field of the sociology of knowledge, particularly the work of Dowling, to begin a discussion around the concept of an historical gaze. I argue that this concept may provide an analytic tool to help us to keep the inter-twined strands of procedural knowledge and substantive knowledge in history from unraveling and coming apart.